Helmet use in connecticut motorcycle crashes: A state without a universal helmet law - Landman, A.B.; Phipps, M.S.; Jawin, K.; Bolton, L.; Van Gelder, C.M.; Kamin, R.; Teel, B.; Vaca, F.E. (Connecticut Medicine, 2011)
Objectives: Assess the association of helmet use with motorcycle crash mortality and identify characteristics of riders who do not wear helmets in Connecticut crashes. Methods: Police crash data for Connecticut motorcycle crashes 2001-2007 were analyzed. Bivariate analysis and multivariable logistic regressions were performed including age, gender, seating position, road type, season, time of day, and recklessness. Results: Of the 9,214 crashes with helmet use data available, helmets were worn in 4,072 (44.2%). Non-helmeted riders, age > 18, riding interstate or state roads, in the evening or at night, and whowereridingrecklesslywere associated withhigher odds of fatality. Predictors of nonhelmet use included males, passengers, age <18 or 30 to 59, and riding in the summer, evening or at night, and on US, state, and local roads. Conclusion: Current crash data affirm that helmets reduce fatal crashes in Connecticut. A set of factors help predictnon helmeted riders to whom safety training could be targeted.
Keywords: Accidents; Traffic; Adolescent; Adult; Age Factors; Connecticut; Craniocerebral Trauma; Female; Head Protective Devices; Humans; Logistic Models; Male; Middle Aged; Motorcycles; Risk Factors; Risk-Taking; Sex Factors; United States; adolescent; adult; age; article; dept.pch; female; head injury; helmet; high risk behavior; human; legal aspect; male; middle aged; mortality; motorcycle; risk factor; sex difference; statistical model; statistics; traffic accident; utilization review; ⛔ No DOI found

Challenges in recruiting minority-serving private practice primary care physicians to a quality improvement project - Meehan, Jr., Thomas P.; Van Hoof, Thomas J.; Galusha, Deron; Barr, Judith K.; Curry, Maureen; Kelvey-Albert, Michele; Meehan, Thomas P. (American Journal of Medical Quality, 2011)
The objectives of this study were the following: (1) describe one organization's experience with recruiting minority-serving private practice primary care physicians to an ambulatory quality improvement (QI) project; (2) compare and contrast physicians who agreed to participate with those who declined; and (3) list incentives and barriers to participation. The authors identified eligible physicians by analyzing Medicare Part B claims data, a publicly available physician database, and office staff responses to telephone inquiries. The recruitment team had difficulty identifying, contacting, and recruiting eligible physicians. Solo practitioners and physicians who had lower scores on certain quality measures were more likely to participate. Barriers to participation were similar in all practices and included concerns about extra work, difficulty of change, and impact on office work flow. Commonly used incentives were offered but were not universally embraced. Additional work is required to refine the process of physician recruitment and to find more compelling incentives for QI.
3 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000294067900004
Keywords: African American; African Americans; Diabetes Mellitus; Hispanic; Hispanic Americans; Humans; Medicare Part B; Personnel Selection; Physicians; Primary Care; Quality Improvement; United States; article; dept.pch; diabetes mellitus; general practitioner; human; medicare; minority; organization and management; personnel management; primary care physicians; quality improvement; recruitment; statistics; total quality management; underserved

The impact of youth and family risk factors on service recommendations and delivery in a school-based system of care. - Whitson, Melissa L; Connell, Christian M; Bernard, Stanley; Kaufman, Joy S (Journal of Behavioral Health Services & Research, 2011)
The present study examines the impact of child and family risk factors on service access for youth and families in a school-based system of care. Regression analyses examined the relationships between risk factors and services recommended, services received, and dosage of services received. Logistic regression analyses examined the relationship between risk factors and whether or not youth received specific types of services within the system of care. Results revealed that youth with a personal or family history of substance use had more services recommended than youth without these risk factors, while youth with a family history of substance use received more services. Youth with a history of substance use received a significantly higher dosage of services overall. Finally, history of family mental illness was associated with receiving mental health and operational services (e.g., family advocacy, emergency funds). Implications and limitations are discussed.
5 citations (Crossref) [2023-10-31] Place: United States Whitson, Melissa L. Department of Public Health, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. melissa.whitson@yale.edu
Keywords: *Adolescent Health Services/sn [Statistics & Numerical Data]; *Mental Health Services/sn [Statistics & Numerical Data]; *School Health Services/sn [Statistics & Numerical Data]; *Substance-Related Disorders/px [Psychology]; Adolescent; Adolescent Health Services; Connecticut; Cross-Sectional Studies; Family Characteristics; Female; Health Services Needs and Demand; Humans; Income; Logistic Models; Male; Mental Health Services; Parents; Questionnaires; Referral and Consultation; Referral and Consultation/sn [Statistics & Numerical Data]; Risk Factors; School Health Services; Schools; Substance-Related Disorders; Substance-Related Disorders/th [Therapy]; Surveys and Questionnaires; United States; addiction; adolescent; article; child health care; cross-sectional study; dept.pch; family size; female; health service; human; income; male; mental health service; parent; patient referral; psychological aspect; questionnaire; risk factor; school; school health service; statistical model; statistics; utilization review

Identification of common and cell type specific LXXLL motif EcR cofactors using a bioinformatics refined candidate RNAi screen in Drosophila melanogaster cell lines - Davis, Melissa B.; SanGil, Inigo; Berry, Grace; Olayokun, Rashidat; Neves, Lori H. (BMC Developmental Biology, 2011)
Background: During Drosophila development, titers of the steroid ecdysone trigger and maintain temporal and tissue specific biological transitions. Decades of evidence reveal that the ecdysone response is both unique to specific tissues and distinct among developmental timepoints. To achieve this diversity in response, the several isoforms of the Ecdysone Receptor, which transduce the hormone signal to the genome level, are believed to interact with tissue specific cofactors. To date, little is known about the identity of these cofactor interactions; therefore, we conducted a bioinformatics informed, RNAi luciferase reporter screen against a subset of putative candidate cofactors identified through an in silico proteome screen. Candidates were chosen based on criteria obtained from bioinformatic consensus of known nuclear receptor cofactors and homologs, including amino acid sequence motif content and context. Results: The bioinformatics pre-screen of the Drosophila melanogaster proteome was successful in identifying an enriched putative candidate gene cohort. Over 80% of the genes tested yielded a positive hit in our reporter screen. We have identified both cell type specific and common cofactors which appear to be necessary for proper ecdysone induced gene regulation. We have determined that certain cofactors act as co-repressors to reduce target gene expression, while others act as co-activators to increase target gene expression. Interestingly, we find that a few of the cofactors shared among cell types have a reversible roles to function as co-repressors in certain cell types while in other cell types they serve as co-activators. Lastly, these proteins are highly conserved, with higher order organism homologs also harboring the LXXLL steroid receptor interaction domains, suggesting a highly conserved mode of steroid cell target specificity. Conclusions: In conclusion, we submit these cofactors as novel components of the ecdysone signaling pathway in order to further elucidate the dynamics of steroid specificity. © 2011 Davis et al; licensee BioMed Central Ltd.
8 citations (Crossref) [2023-10-31] Citation Key Alias: pop00119 tex.type: [object Object]
Keywords: Amino Acid Motifs; Animals; Co-Repressor Proteins; Computational Biology; Drosophila melanogaster; Ecdysone; Phylogeny; RNA Interference; RNA interference; Receptors; Steroid; Transcription Factors; animal; article; biology; chemistry; corepressor protein; dept.pch; ecdysone; ecdysone receptor; genetics; metabolism; phylogeny; protein motif; steroid receptor; transcription factor